Experimental Study on the Damage of Artificial Fracture Permeability in Coal during the Flow Back of Guar-Based Fracturing Fluid - Shenggui Liu; Jinkuang Huang; Songlei Tang; Shixiong Shi; Xuan Wu; Xin Liu (Geofluids)
After the completion of fracturing operation in coalbed methane (CBM), the fracturing fluid needs to flow back to the ground in time to reduce the damage to the coal reservoir. The damage of guar-based fracturing fluid to the coal reservoir has an adverse effect on the fracturing stimulation. A series of flow experiments were carried out with the unconventional natural gas reservoir damage evaluation equipment. This paper investigates the evolution of fracture permeability in coal samples during the process of hydroxypropyl guar (HPG) fracturing fluid flow back. The experimental results show that the fracturing fluid concentration, proppant type, proppant particle size, and proppant concentration all affect fracture permeability. The high concentration of fracturing fluid caused irreversible damage to fracture permeability of coal samples. With the increase of fracturing fluid concentration, the permeability damage rate increased from 65.31% to 84.57%, and the damage degree was strong. KCL brine flushing can only decrease the damage rate of coal sample fracture permeability within a certain range. The proppant embedment and the generation of pulverized coal exacerbated the damage of fracture permeability. The research results can be beneficial for optimizing the type and performance of fracturing fluid for hydraulic fracturing in CBM reservoir.